2019
DOI: 10.48550/arxiv.1911.00092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Logarithmic variance for the height function of square-ice

Abstract: In this article, we prove that the height function associated with the square-ice model (i.e. the six-vertex model with a = b = c = 1 on the square lattice), or, equivalently, of the uniform random homomorphisms from Z 2 to Z, has logarithmic variance. This establishes a strong form of roughness of this height function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…For the result on the square ice, we also refer to [10]. It was later shown that conditional on this delocalisation, the delocalisation is logarithmic: the previously mentioned dichotomy result [14]. These results have recently been extended to the more general six-vertex model for a = b = 1 and 1 ≤ c ≤ 2, see [15].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…For the result on the square ice, we also refer to [10]. It was later shown that conditional on this delocalisation, the delocalisation is logarithmic: the previously mentioned dichotomy result [14]. These results have recently been extended to the more general six-vertex model for a = b = 1 and 1 ≤ c ≤ 2, see [15].…”
Section: Introductionmentioning
confidence: 83%
“…Second, we demonstrate that the absolute value of the height function satisfies the FKG lattice condition whenever nonnegative boundary conditions are imposed (Theorem 2.8). The property holds true for both the solid-on-solid model as well as for the discrete Gaussian model, and may be of independent interest given the recent successes that it has had in the context of the square ice and the six-vertex model in proving logarithmic delocalisation [14,15]. The general strategy of these articles stems from an older work [17] where the FKG lattice condition is used to prove a dichotomy for the quantitative behaviour at and off criticality in the random-cluster model.…”
Section: Introductionmentioning
confidence: 92%
“…The work [31] extends this result to prove that the variance is of order log(L). It is further conjectured that the scaling limit of h L is the continuum Gaussian free field, and that the level lines of h L (see Figure 3) scale to the Conformal Loop Ensemble (CLE) with parameter κ = 4.…”
Section: Height Functionmentioning
confidence: 67%
“…which is a form of correlation decay. While (19) does not distinguish between the disordered and critical cases (in the sense discussed in Section 1.2), recent work of Duminil-Copin-Harel-Laslier-Raoufi-Ray [31] can be used to obtain a rate of convergence in (19),…”
Section: Constant Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation